Pengaruh Non Performing Financing (NPF) Terhadap Return On Assets (ROA) Pada Bank Syariah Indonesia - Amimah Qodari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effect of non-performing financing (NPF) on profitability at Indonesian Islamic Banks before and after the merger. This study examines the effect of non-performing financing (NPF) on return on assets (ROA). The population used in this study are Islamic banks that have merged, namely BNI Syariah, BRI Syariah, and Bank Syariah Mandiri for the period 2017-2021. The sample used in this study is the Indonesian Sharia Chapter (BSI) which publishes an annual report in the 2017-2021 period. The research data is secondary data, obtained from the BSI website which is the research sample. While the data analysis method used is multiple linear regression analysis. The results of this study indicate that the NPF variable has an effect on ROA of 8.4% with a significance level of 0.361. Keywords : Non Performing Financing (NPF), Return On Assets (ROA)